Legislation as an Effort to Oppose the Exploitation of Underage Workers in the Perspective of Human Rights - Sugeng Samiyono; Faisal Santiago; Evita Isretno Israhadi (Pusat Publikasi Nusantara, 2023)
The current phenomenon is often found in children becoming laborers or workers in home industries. Some of the dominant factors causing children to become laborers were found in the field, including family, environmental influences, local potential and recruitment patterns, educational needs and future orientation, and encouragement from the children themselves. Meanwhile, the reason why employers use children as labor is caused by several things, among others, because the child comes personally to the entrepreneur, offers labor, to enter a child laborer generally through informal procedures, the workforce will be easy to manage and obedient when compared to with adult workers or for reasons of pity/pity rather than being neglected to work on the streets where the conditions are very dangerous, it is better to be recruited as workers. The philosophy of prohibiting children from working or employing children as regulated in the Manpower Law is closely related to efforts to protect children's human rights, which are also guaranteed protection in Law No. 39 of 1999 on Human Rights. Provisions that prohibit the employment of children as regulated in the provisions of Article 68 of the Manpower Law are in line with the provisions of Article 52 paragraph (1) of Law No.39 of 1999 concerning Human Rights, which stipulates that every child has the right to protection by parents, family, community and country. Law Number 23 of 2002, Article 1 Paragraph 2 states that child protection is all activities to guarantee and protect children and their rights so that they can live, grow, develop and participate optimally by human dignity and protection, receive protection from violence and discrimination.